Diagnóstico e avaliação exploratória inicial dos avanços dos objetivos de desenvolvimento sustentável no campus Lagoa do Sino - Ribeiro, Gleyce Kelly (Universidade Federal de São Carlos, 2024)
In the context of the current global scenario, the 2030 Agenda and the Sustainable Development Goals (SDGs) have become highly relevant topics on academic and social agendas. Higher Education Institutions (HEIs), with their role as generators and disseminators of knowledge, have a responsibility to present sustainable solutions, provide assistance in fulfilling the SDGs and share their initiatives. The aim of this study is to carry out an initial diagnosis of the inclusion of the SDGs at the Lagoa do Sino Campus of the Federal University of São Carlos (UFSCar). To this end, an bibliographical survey was carried out of the main SDG indicators used by HEIs. At the same time, an initial diagnosis of the inclusion of the SDGs on the Lagoa do Sino Campus was carried out, by mapping the initiatives linked to the SDGs and published in UFSCar's Activity Reports and Annual Management and Activity Reports in 2020, 2021 and 2022. Through the mapping, it was possible to propose indicators consistent with the institution's scenario to assess the SDGs and recommend improvement actions for their more appropriate inclusion. The results of the survey culminated in the identification of 61 SDG assessment indicators most commonly used in HEIs, 43% of which are associated with SDG 4 - Quality Education. During the mapping process, it was possible to identify 79 initiatives linked to the SDGs, ranging from institutional policies to cultural events, which are practiced on campus. By correlating the indicators obtained in the literature survey with the initiatives mapped, it was possible to determine 47 indicators that can be used to assess the inclusion of the SDGs on the Lagoa do Sino campus. Of the 61 indicators obtained, 14 were not considered applicable due to the lack of SDG-related activities disclosed in the reports. To help the institution implement initiatives to address these non-applicable indicators, improvement actions were presented, such as a Diversity and Equity Census and a Greenhouse Gas Emissions Inventory. The implementation and measurement of these indicators will result in greater transparency in the disclosure of results in relation to meeting the targets of certain SDGs, highlighting the institution's maturity in the pursuit of sustainability.
Diagnosis and initial exploratory evaluation of advances in sustainable development goals at the Lagoa do Sino campus
Keywords: Objetivos de desenvolvimento sustentável; Indicadores de ODS; Instituições de ensino superior; Agenda 2030; SDG indicators; Sustainable development goals; Higher education institutions; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL